2022
DOI: 10.15240/tul/001/2022-2-008
|View full text |Cite
|
Sign up to set email alerts
|

Do Service Quality and Social Media Marketing Improve Customer Retention in Hotels? Testing the Mediation Effect

Abstract: Customer retention is a critical factor in companies’ survival, and both service quality and social media are important means of retaining customers. However, despite this importance of these antecedents, only a few studies considered the effects of these factors in the hotel industry literature. With the application of social exchange theory, the current research aims to evaluate the effect of service quality and social media marketing on customer retention in hotels, and evaluates how customer satisfaction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The respondents confirmed that the use of social media makes the brand more popular among foreigners, as brand awareness plays an important role in customer satisfaction (Cheraghalizadeh & Dědková, 2022). Furthermore, the respondents mentioned that social media is helpful in providing information about the company's services and benefits, obtaining comments from guests and the hotel's reputation, as well as the exchange of information about prices and promotions, in addition to information about the hotel chain.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…The respondents confirmed that the use of social media makes the brand more popular among foreigners, as brand awareness plays an important role in customer satisfaction (Cheraghalizadeh & Dědková, 2022). Furthermore, the respondents mentioned that social media is helpful in providing information about the company's services and benefits, obtaining comments from guests and the hotel's reputation, as well as the exchange of information about prices and promotions, in addition to information about the hotel chain.…”
Section: Resultsmentioning
confidence: 79%
“…Furthermore, 100% of the respondents stressed that social networks have contributed to brand awareness, indicating that "it has been possible to reach many more people, many more potential customers all over Peru" (Lambayeque Manager, personal communication, May 2, 2023). Cheraghalizadeh & Dědková (2022), indicated that social network marketing helps with customer retention.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of Mustika & Farid identified that Social Media Marketing has a positive effect on Customer Retention (Mustika & Farid, 2022). In the results of previous studies, it shows that Social Media Marketing affects Customer Retention (Cheraghalizadeh & Dědková 2022;Menajang et al 2023).…”
Section: Relationship Of Variablesmentioning
confidence: 91%
“…The gap related to this research is that previous research succeeded in the overview perspective and did not explore the concepts and understanding related to Customer Retention. In previous research (Bozkurt et al 2021;Cheraghalizadeh & Dědková, 2022;Hidayat & Martini 2020;Joshi et al2022;Ramadhanty & Mei Ulina Malau, 2020;Sashi et al 2019;Vohra & Bhardwaj, 2019) shows different aspects of variables, it is rare to find research that examines Social Media Marketing on Customer Retention mediated by Customer Engagement. Based on the explanation above, this research aims to determine the effect of Social Media Marketing on Customer Retention with Customer Engagement as a Mediating Variable on e-commerce users.…”
Section: Introductionmentioning
confidence: 99%